Comparative Evaluation of Subgingivally Delivered Tetracycline Fibers and Aloe Vera Gel as an Adjunct to Scaling and Root Planing in Treatment of Chronic Periodontitis: A Randomized Controlled Clinical Trial - Anurag Thakuria; Swati Agarwal; Ellora Madan; Kratee Sharma; Zaby Fatima (Journal of Pharmacy and Bioallied Sciences)
Introduction: Comprehensive mechanical debridement, like scaling and root planing (SRP), combined with proper plaque control, is the primary nonsurgical approach for managing periodontitis. However, it may not always eliminate infection due to inadequate debridement or inaccessible areas. For this, various chemotherapeutic allopathic and herbal local drug delivery (LDD) agents as adjuvants have been used with SRP for management of chronic periodontitis. Methodology: A randomized controlled clinical trial was conducted, comprising 60 sites from 20 patients. Each patient received three treatment modalities assigned to different quadrants: SRP with normal saline irrigation, SRP with LDD of tetracycline fibers, and SRP with LDD of 100% pure aloe vera gel. Clinical parameters were assessed at baseline, day 7, and 3 months postoperatively. Results: The addition of 100% pure aloe vera gel and tetracycline fibers (Periodontal Plus ABTM) with SRP significantly improved the probing pocket depth (P < 0.05) compared to SRP with saline irrigation. Additionally, the tetracycline group showed significant reductions in plaque index (P < 0.05) and highly significant reductions in modified sulcular bleeding index (P < 0.001) compared to the saline group. Conclusion: Aloe vera gel with SRP shows comparable effectiveness to tetracycline fibers in managing chronic periodontitis, suggesting it as a cost-effective herbal alternative.